Pyoderma Gangrenosum, Acne, and Hidradenitis Suppurativa Syndrome: A Case Report and Literature Review - Huang, Jundong; Tsang, Lemuel Shui-Lun; Shi, Wei; Li, Ji (Frontiers in Medicine, 2022)
PASH syndrome is a rare inflammatory disease characterized by pyoderma gangrenosum (PG), mild to severe facial acne and hidradenitis suppurativa (HS). It seems to only affect the skin organ and represents a cutaneous characteristics of the spectrum of autoinflammation. Lack of pyogenic sterile arthritis (PA) distinguishes PASH syndrome from PA-PASH (pyogenic arthritis, pyoderma gangrenosum, acne and hidradenitis suppurativa), PASS (pyoderma gangrenosum, acne, hidradenitis suppurtiva and ankylosing spondylitis) and PAPA (pyogenic arthritis, pyoderma gangrenosum and acne) syndromes. The exact etiology and pathogenesis of PASH syndrome remain unknown. Both PG and HS are contained in the spectrum of neutrophilic dermatitis, which is now considered to be an autoinflammatory syndrome. From a pathophysiological point of view, they show same mechanisms include overexpression of the interleukin-1(IL-1) family and neutrophil-rich cutaneous infiltration. These findings provide guidance for treating this intractable disease. We here describe a case of PASH syndrome and the patient failed to respond to immunosuppressive treatment initially, whereas all skin lesions rapidly relieved after receiving treatment of colchicine and thalidomide. We review the literature for previously reproted cases, focusing emphatically on its treatment.